Characteristics of Slovenian Adults in Community-Based Whole-Food Plant-Based Lifestyle Program - Boštjan Jakše; Barbara Jakše; Stanislav Pinter; Jernej Pajek; Nataša Fidler Mis (Journal of Nutrition and Metabolism)
Objective. Adopting a plant-based diet (PBD) and lifestyle is healthy, sustainable, and increasingly popular, while also demanding. Individuals might face challenges to maintain this lifestyle. We aimed to determine the anthropometric values and lifestyle factors and motives of adults to adopt a whole-food, plant-based (WFPB) lifestyle by joining our ongoing, community-based, WFPB lifestyle program 0.5–10 years ago. Methods. We measured body mass index (BMI) and body fat percentage status (BF%) using bioimpedance. Lifestyle status was obtained by standardized electronic questionnaires. For evaluating the motives for following strict PBD, the participants were asked to rank 8 different motives (i.e., 8: the most-, 1: the least important). Setting. A cross-sectional study in Slovenia. Participants. A total of 151 healthy adults with an average age of 39.6 years (SD: 12.5 years). Results. The participants had an average BMI of 23.9 kg/m2 (SD: 3.8 kg/m2) and an average BF% of 22.3% (SD: 7.3%), were physically very active, with an average Long International Physical Activity Questionnaire (L-IPAQ) score of 5541.2 metabolic equivalents (METs) min/week (SD: 4677.0 METs min/week), having good sleep quality, with an average Pittsburgh Sleep Quality Index (PSQI) score of 2.7 (SD: 1.8), perceiving low stress, and with an average Perceived Stress Questionnaire (PSQ) score of 0.29 (SD: 0.1). We discovered no significant differences in lifestyle between participants who were involved in our WFPB lifestyle program for short, medium, or long periods of time. The motives for WFPB lifestyle included health benefits (score: 7.9/8), body mass management (6.3), eating to satiety (4.9), convenience (4.3), environmental concerns (4.1), affordability (3.7), animal ethics (3.6), and religious reasons (1.1). Conclusion. A WFPB lifestyle program for any length of time that includes an extensive support system provides favorable, long-term lifestyle changes.